“Qa’idojin Rubutun Hausa, Ga Qoshi Ga Kwanan Yunwa” - Muhammad Bugaje, Hauwa (International Journal of Arts, Languages, Linguistics and Literary Studies, 2023)
Hausa is language that is blessed with a lot of works of scholars on the issue of its orthography and standardization. There is no language in Nigeria that is even close to Hausa in terms of standardization of its orthography. Hausa language was initially written in Ajami after the advent of Islam in Hausa Land, later, Hausa language was also benefitted with modernism and the way of writing brought by colonial masters. The colonial masters and Hausa Scholars introduced the standard way of writing through their publications and conferences in and outside the country. This paper reviews the effort scholars in standardizing Hausa writing, and the problems that are encountered by the users and the students in writing the language especially now with the advent of technology and globalizations. The paper also recommends ways that can be considered in improving good writing among Hausa’s especially at the academic level.